Reading with feeling : affect theory and the Bible - Black, Fiona C.; Koosed, Jennifer L. (Semeia studies;, 2019)
"The psychological approach known as affect theory focuses on bodily feelings-depression, happiness, disgust, love-and can illuminate both texts and their interpretations. In this collection of essays scholars break new ground in biblical interpretation by deploying a range of affect-theoretical approaches in their interpretations of texts. Contributors direct their attention to the political, social, and cultural formation of emotion and other precognitive forces as a corrective to more traditional historical-critical and linguistic interpretive methods, and response essays push the conversations into profitable directions for future research"--